I am Trans and Catholic exploring the lived experiences of religiosity and identity negotiation of transwomen - Delicias, Mary Dio Anne A.
Transwomen are widely visible in the Philippines. However, there is limited literature on their experiences in this predominantly Catholic country. This qualitative research explored the lived experiences of religiosity and the processes of identity negotiation among Filipino Catholic Transwomen. Using Interpretative Phenomenological Analysis (IPA) as a framework, semi-structured interviews were conducted among six practicing Catholic Transwomen. This study showed that Filipino Catholic transwomen experience discrimination, ambivalent acceptance, and religious-trans identity agreement. Underscored here are the intersections between Filipino transwomen's religious and trans identities. This research contributes to the corpus of evidence on transwomen's identity negotiation within a religious context. Keywords: transwomen, lived experiences, religiosity, identity negotiation, Interpretative Phenomenological Analysis.
Research, Undergraduate, UPV Miag-ao, Bachelor of Arts in Psychology
Keywords: Transwomen; Religiosity; Interpretative Phenomenological Analysis